2019
DOI: 10.3201/eid2601.190778
|View full text |Cite
|
Sign up to set email alerts
|

Infectivity of Norovirus GI and GII from Bottled Mineral Water during a Waterborne Outbreak, Spain

Abstract: During a waterborne outbreak of norovirus in Spain, we estimated 50% illness doses for a group of exposed (secretor) persons to be 556 (95% CI 319–957) genome copies/day for norovirus GI and 2,934 (95% CI 1,683–5,044) genome copies/day for norovirus GII. Use of a propidium monoazide viability assay reduced these values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…FUT2 genotyping allowed us to identify 18 nonsecretor subjects who had HuNoV shedding in stool, confirming their infection status, with presentation of acute gastroenteritis symptoms in all of them but one. While symptomatic infection of HuNoV in nonsecretors has been documented for GI.2, GI.3, GII.1, GII.2, GII.3, GII.6, GII.7, GII.4, and GII.17 genotypes [7][8][9], our report confirms for the first time infection by the GI.4 genotype as well, with sequence confirmation in stool. Binding of GI.4 viruses to carbohydrates from secretor-negative individuals has been documented in vitro [31], but to our knowledge, natural infections have not been reported yet.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…FUT2 genotyping allowed us to identify 18 nonsecretor subjects who had HuNoV shedding in stool, confirming their infection status, with presentation of acute gastroenteritis symptoms in all of them but one. While symptomatic infection of HuNoV in nonsecretors has been documented for GI.2, GI.3, GII.1, GII.2, GII.3, GII.6, GII.7, GII.4, and GII.17 genotypes [7][8][9], our report confirms for the first time infection by the GI.4 genotype as well, with sequence confirmation in stool. Binding of GI.4 viruses to carbohydrates from secretor-negative individuals has been documented in vitro [31], but to our knowledge, natural infections have not been reported yet.…”
Section: Discussionsupporting
confidence: 75%
“…However, despite not being a widespread phenomenon, the occurrence of HuNoV RNA in saliva opens the door to a possible oral-oral transmission. Although the RNA concentrations of the virus in saliva appear to be much lower than those present in feces, or vomit, given the low infectious dose described for HuNoV [8,[43][44][45], concentrations could be high enough to infect a new host. In addition, using the PMA-RTqPCR viability assay we confirmed that saliva may contain a high proportion of viruses with intact capsids, thus being potentially infectious.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it should be read with caution that viral RNA level does not equal the amount of infectious virus. In a very recent study, by using viability PCR, it was revealed that only around 5% of all norovirus RNA genomes detected by qPCR came from intact virions [ 51 ]. Interestingly, one study revealed that HuNoV particles were packed within exosome-derived small vesicles of less than 200 nm [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…GII strains account for ~90% of infections and occur earlier in life than GI infections [122,123]. Infection follows a fecal-oral route, with infection possible with small amounts of virion exposure [124][125][126][127]. Once infected, children may shed virus for weeks post-infection [128].…”
Section: Virus Backgroundmentioning
confidence: 99%